Bread, Water, Book And Library - Coşkun Polat (Türk Kütüphaneciliği)
Reading is a process of communication, perception, learning and development. Reading, informing and learning; it is a basic necessity for human being as much as nutrition and welfare. With the information he possesses, person can reveal his individual attitude, his intellectual infrastructure and his touch of life. Reading from the most priority means of informing action is both a personal and a social element of culture. Reading always means a positive attitude for individuals and societies and it is considered the starting point of thinking, researching, questioning and producing. The resulting profit of the reading and thinking society is freedom, productivity and development. When someone talks about reading, books come to mind. The book, yesterday and today, has become the most basic means of reading and informed. Libraries are the common good of books and people. Libraries working to ensure that reading, information, and the book are at the center of human life, are an indispensable actor in supporting social and cultural development of formal education, and in teaching non-formal education. This book titled "Bread, Water, Book and Library" was written by associate professor Erol Yılmaz in order to raise awareness about reading, information, books and the library in Turkish society. In this work, about topics of reading habit, reading culture, book, library are written in a fluent and literary style.